The relationship between nutrition adequacy level, physical activity, and pregnancy outcomes in mothers and infants - Hamidah Aula Rusydiana; Mira Dewi; Hadi Riyadi; Lilik Kustiyah (AcTion: Aceh Nutrition Journal, 2023)
Pregnancy outcomes are affected by many factors: nutrition and physical activity. This study aims to determine the relationship between physical activity and nutritional adequacy level of pregnant women in the third trimester with pregnancy outcomes, namely maternal fasting blood glucose levels, blood pressure and amniotic fluid volume, and baby's birth weight and length. An observational study on a cohort was conducted on 34 pregnant women in their third trimester and followed until delivery in the Ciampea sub-district, Bogor, Indonesia. The data were processed through descriptive analysis for each variable. Bivariate tests between the predictor and outcome variables were performed using Pearson's correlation and Multiple Regression at 95% CI. Based on multiple regression analysis, we found that the samples' fasting blood glucose in the third trimester was predicted to be 36,9% positively affected by pre-pregnancy body mass index (b= 2,521; p= 0,009) and total physical activity during the third trimester (b= 0,055; p= 0,006). In conclusion, the nutritional adequacy level of macronutrients in the third trimester has not yet significantly affected pregnancy outcomes in this study. It is suggested that pregnant women should avoid prolonged sedentary activity and increase appropriate exercise to achieve maternal health and improve birth outcomes.